Спосіб обробки вкладишів підшипників ковзання - Тарельник, В'ячеслав; Дзюба, Олександр (КІНПАТРІ ЛТД, 2013)
Improving the reliability and durability of bearings by improving their running-babbitt liners.
Method for processing brasses sliding